2004
DOI: 10.1086/422000
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Patients with Crimean-Congo Hemorrhagic Fever in a Recent Outbreak in Turkey and Impact of Oral Ribavirin Therapy

Abstract: We describe the epidemiological, clinical, and laboratory findings and the role of ribavirin therapy for 35 patients who received a diagnosis of Crimean-Congo hemorrhagic fever (CCHF). All patients had immunoglobulin M antibodies and/or PCR results positive for CCHF virus in blood or tissue specimens. Eighty-six percent of the patients were considered to have severe cases of CCHF. The overall case-fatality rate was 2.8%. Eight patients were given ribavirin, and all 8 survived. We suggest using ribavirin to tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
216
2
30

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(262 citation statements)
references
References 13 publications
14
216
2
30
Order By: Relevance
“…14,[27][28][29][30] In a historical cohort study in Iran, we concluded that oral ribavirin is an effective treatment of the hemorrhagic form of CCHF. 9 Prophylaxis is suggested after high-risk contamination.…”
Section: T Able 1 Laboratory Findings Of Three Nosocomial Cases Of Crmentioning
confidence: 99%
“…14,[27][28][29][30] In a historical cohort study in Iran, we concluded that oral ribavirin is an effective treatment of the hemorrhagic form of CCHF. 9 Prophylaxis is suggested after high-risk contamination.…”
Section: T Able 1 Laboratory Findings Of Three Nosocomial Cases Of Crmentioning
confidence: 99%
“…6 In trials conducted on CCHF, leukocytosis, elevated ALT and AST, PT and aPTT and LDH (lactate dehydrogenase) values were used in assessing prognosis. 4,11,12 No information is available in the literature indicating the role of blood groups in the prognosis of CCHF. In the current trial, high ALT and AST levels and low leukocyte and platelet values were observed, in accordance with the results of other trials.…”
Section: Discussionmentioning
confidence: 99%
“…They realized that dyspnoea and cough were common symptoms, but haemoptysis was only present in Discussion CCHF incidence and prevalence have increased recently with more than 1000 cases reported from southeastern Europe and western Asia each year [9]. This is important because fatality rates in hospitalized patients have reached approximately 50% and death occurs mainly due to disseminated intravascular coagulation and multi organ failure [11][12][13][14][15][16][17][18][19][20][21]. There are no specific treatment or vaccine prophylaxes at this moment.…”
Section: Evidencesmentioning
confidence: 99%
“…It can last up to 9 days when the disease is acquired through a tick bite and a maximum of 13 days when transmission occurs by infected tissues or blood [3]. Next, the pre-haemorrhagic period involves a broad-albeit non-specific range of symptoms such as fever, chills, severe headache, photophobia, myalgia, abdominal pain, nausea, flushing, hypotension, and bradycardia [17,18]. The haemorrhagic stage can develop as soon as 3 days into the disease [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation